PENGELOLAAN DANA MASYARAKAT OLEH BADAN PENYELENGGARAAN JAMINAN SOSIAL (BPJS) KESEHATAN: Tinjauan Konsep Asuransi Islam Terhadap Keberadaan Unsur Ribawi dan Garar - Amri, Aulil; Iyasi, Minny (Al-Iqtishadiah: Jurnal Hukum Ekonomi Syariah, 2021)
This study examines the Management of Public Funds by the Health Social Security Administration (BPJS) (Review of the Concept of Islamic Insurance Against the Existence of Riba and Garar Elements). The problem that will be studied in this research is how is the health management system for public funds (BPJS) and how is the health social fund management system (BPJS) for health, and how is the existence of ribawi and garar elements in the management of public funds at BPJS Kesehatan. In this study, the authors use qualitative research with field research methods by visiting the BPJS Health office and conducting observation and interview techniques, and library research methods by reviewing books, journals and other data that support this research. The conclusions in this study indicate that in the current management of BPJS Health, there are actually many that are in accordance with sharia principles such as the principle of mutual cooperation used by BPJS Health is the same as the ta'awun contract in sharia insurance. In terms of fund management, BPJS has made it clear about public funds by including the registration requirements as suggested by the MUI. Regarding the late penalty which was previously applied by BPJS Kesehatan as much as 2%, this has been abolished since 2016 with the issuance of Presidential Regulation No. 19 of 2016 concerning the Second Amendment to Presidential Regulation No. 12 of 2013. In 2020 President Joko Widodo stipulates Presidential Regulation number 64 of 2020. Article 42 states that BPJS Kesehatan does not apply a penalty system for late payment of contributions. However, regarding investment in public contributions, until now they still use conventional investments and deposit funds also use conventional banks which still contain usury.